Utility Value-Based User′s Preference Evaluation to Select Design Alternatives for Customized Apartment Housing Remodeling. Issue 2 (1st May 2018) - Hong, Eunhwa; Cho, Jaeho; Chun, Jaeyoul
Abstract : As an alternative method for architectural regeneration, remodeling is drawing keen attention. However, it has turned out that post-occupancy satisfaction is quite low. The main reason for the low satisfaction lies in the remodeling method that does not consider functions demanded by users, but carries it out in an expensive and uniform structure. As for architectural function, multiple functions are required to meet resident′s demands for performance and functional values are apt to conflict with each other, which means when one function improves, others are limited in terms of value. Therefore, user requirements should be well defined to increase their satisfaction while considering functions in conflict. In this respect, the present study proposes a method for user preference evaluation to define functions that a user requires, and thus for maximizing the values of remodeling by improving user satisfaction and residential performance.